The Role of Milk on Children's Weight Status: An Epidemiological Study among Preadolescents in Greece - Aikaterini Kanellopoulou; Rena I. Kosti; Venetia Notara; George Antonogeorgos; Andrea Paola Rojas-Gil; Ekaterina N. Kornilaki; Areti Lagiou; Mary Yannakoulia; Demosthenes B. Panagiotakos (MDPI AG, 2022)
Milk consumption contributes greatly to children's diet, playing a pivotal role in the development and structure of bones and the functioning of the musculoskeletal system and the heart. This study investigated the association between the type of milk and childhood overweight/obesity. In the school period 2014-2016, 1728 students aged 10-12 years and their parents participated. The measurement and classification of their weight status were performed through the criteria of the International Obesity Task Force. Among others, the type of milk consumption was recorded. Four categories of the type of milk children consumed were classified (white milk, chocolate milk, both types of milk, and no milk at all). Children consuming only white milk were 33.1% less likely to be overweight/obese in comparison with children who were not consuming milk at all [OR (95% CI): 0.669 (0.516, 0.867), p = 0.002]. The consumption of chocolate milk showed a protective role against childhood overweight/obesity although its association was not consistently significant. This study highlights the significant contribution of milk (and particularly of white milk) consumption to weight management, and thus its promotion should be consistently encouraged. More studies are needed to shed light on the effects of different dairy foods on weight status in childhood.